PREPARATION OF Ni1-xMnxFe2O4 FERRITES BY SOL-GEL METHOD AND STUDY OF CATION DISTRIBUTION - Abbas, Tahir; Hussain, Abid; Niazi, Shahida B. (Journal of Research (Science), 2025)
The nanoparticles of the spinel ferrite system Ni1-xMnxFe2O4 with x=0.0, 0.1, 0.3, 0.5, 0.7 and 0.9 were prepared by sol-gel combustion technique using chlorides of Ni, Mn and Fe with citric acid as a source. The structure of ferrite materials and the particle size were determined by x-ray diffraction (XRD). It was observed that the structure is single phase, face centered cubic with lattice parameters and the particle size ranging from 8.365Ǻ to 8.394Ǻ and 23.86Ǻ to 38.30Ǻ respectively. The lattice parameter showed a linear dependence on concentration in accordance with the Vegard’s law. By analyzing XRD patterns, the cation distribution over A and B-sites was estimated through R-Factor method. The magnetic moment for each sample was determined from cation distribution on the two sites. An enhancement in the net magnetic moment was observed with gradual increase in the Mn content.